2000
DOI: 10.1146/annurev.pharmtox.40.1.389
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Regulation of Opioid Receptor Signaling

Abstract: Cloning of multiple opioid receptors has presented opportunities to investigate the mechanisms of multiple opioid receptor signaling and the regulation of these signals. The subsequent identification of receptor gene structures has also provided opportunities to study the regulation of receptor gene expression and to manipulate the concentration of the gene products in vivo. Thus, in the current review, we examine recent advances in the delineation basis for the multiple opioid receptor signaling, and their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
430
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(445 citation statements)
references
References 218 publications
6
430
0
7
Order By: Relevance
“…However, the chronic effects of cocaine on the cdk5/p35 complex (upregulation) were mediated through the induction of the transcription factor DFosB (Bibb et al, 2001), and the accumulation of DFosB in brain also has been observed after chronic morphine administration (Nye and Nestler, 1996;Nestler et al, 2001). Owing to the multiple and complex opioid receptor signaling (Law et al, 2000), different molecular mechanisms may account for the downregulation of the cdk5/p35 complex induced by chronic morphine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the chronic effects of cocaine on the cdk5/p35 complex (upregulation) were mediated through the induction of the transcription factor DFosB (Bibb et al, 2001), and the accumulation of DFosB in brain also has been observed after chronic morphine administration (Nye and Nestler, 1996;Nestler et al, 2001). Owing to the multiple and complex opioid receptor signaling (Law et al, 2000), different molecular mechanisms may account for the downregulation of the cdk5/p35 complex induced by chronic morphine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…They are coupled via pertussis toxin-sensitive G i /G o proteins to a variety of effectors that include adenylate cyclase, potassium channels, calcium channels, and mitogen-activated protein kinase pathways {for a review, see [2]}. Morphine acts primarily on the MOR [3] and are among the most widely abused drugs.…”
Section: Introductionmentioning
confidence: 99%
“…These receptors belong to rhodopsin subfamily of 7-transmembrane receptors (7-TMRs)/G-protein-coupled receptors (GPCRs) (Bockaert and Pin, 1999). They are coupled via pertussis toxin-sensitive G i /G o proteins to many downstream effectors such as adenylate cyclase, potassium channels, calcium channels, and a mitogen-activated protein kinase pathway [for a review, see Law et al, 2000]. Although opioid drugs have long been used as analgesics, their clinical use is limited by the fear of addiction and side effects such as respiratory depression, decreased gastrointestinal motility, sedation, mood changes, and tolerance (Kieffer, 1999).…”
Section: Introductionmentioning
confidence: 99%